2019
DOI: 10.3389/fphar.2019.00603
|View full text |Cite
|
Sign up to set email alerts
|

Shen-Yuan-Dan Capsule Attenuates Atherosclerosis and Foam Cell Formation by Enhancing Autophagy and Inhibiting the PI3K/Akt/mTORC1 Signaling Pathway

Abstract: Background and Aim: The phosphoinositide 3-kinase (PI3K)/Akt/mammalian target of rapamycin complex 1 (mTORC1) signaling pathway plays a crucial role in autophagy and inflammation. Our previous studies demonstrated that Shen-Yuan-Dan Capsule (SYDC), a Chinese medicine used for treating angina pectoris, has anti-atherosclerotic and anti-inflammatory effects in mice. However, its effects on autophagy and the PI3K/Akt/mTORC1 signaling pathway remain unclear. This study aimed to explore the effects of SY… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 45 publications
0
27
0
Order By: Relevance
“…It has been demonstrated that PI3K/Akt/autophagy pathway is closely related to the regulation of cells migration and angiogenesis . The results also indicated the down‐regulation and up‐regulation of PI3K and Akt phosphorylation were found in EPCs with miR‐9‐5p mimics and inhibitor, respectively (Figure 5).…”
Section: Resultsmentioning
confidence: 86%
“…It has been demonstrated that PI3K/Akt/autophagy pathway is closely related to the regulation of cells migration and angiogenesis . The results also indicated the down‐regulation and up‐regulation of PI3K and Akt phosphorylation were found in EPCs with miR‐9‐5p mimics and inhibitor, respectively (Figure 5).…”
Section: Resultsmentioning
confidence: 86%
“…There is a study identifying that inhibition of PI3K/AKT/ mammalian target of rapamycin complex 1 (mTORC1) signaling pathway activation partially ameliorates AS evidenced by reduced blood lipid levels and TC content. 21 Currently, up-regulated HULC is proved to ameliorate TNF-α-induced inflammatory injury in osteoarthritis. 18 Besides that, it is previously documented that PI3K/AKT inhibitor LY294002 reduces TNF-α and IL-6 levels in retinopathy.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the study has investigated that HULC lowers blood lipid levels and inhibits inflammatory and oxidative stress‐related factor expression via inactivating PI3K/AKT signaling pathway in AS mice. There is a study identifying that inhibition of PI3K/AKT/mammalian target of rapamycin complex 1 (mTORC1) signaling pathway activation partially ameliorates AS evidenced by reduced blood lipid levels and TC content 21 . Currently, up‐regulated HULC is proved to ameliorate TNF‐α‐induced inflammatory injury in osteoarthritis 18 .…”
Section: Discussionmentioning
confidence: 99%
“…Atherosclerosis is the most common cause of ischaemic heart disease and stroke; it is closely associated with the occurrence of acute cardiovascular events, which have a huge impact on human life and health, accounting for 20% of total mortalities worldwide (1). It is widely known that during the early stages of atherosclerosis, monocytes enter the endothelial layer and differentiate into macrophages under the action of adhesion molecules and cytokines (2)(3)(4). For example, in one previous study, autopsies of patients with atherosclerosis discovered the accumulation of a large number of macrophages, lymphocytes and foam cells in the coronary artery plaques (2).…”
Section: Introductionmentioning
confidence: 99%
“…It is widely known that during the early stages of atherosclerosis, monocytes enter the endothelial layer and differentiate into macrophages under the action of adhesion molecules and cytokines (2)(3)(4). For example, in one previous study, autopsies of patients with atherosclerosis discovered the accumulation of a large number of macrophages, lymphocytes and foam cells in the coronary artery plaques (2). Macrophages are mainly divided into two different subtypes: M1-type macrophages are mainly found in unstable plaques, whereas M2-type macrophages are predominantly found in stable plaque tissue (5,6).…”
Section: Introductionmentioning
confidence: 99%